Effect of the preparation method on structural and in vitro digestibility properties of type II resistant starch-enriched wheat semolina pasta. (July 2022) - Garcia-Valle, Daniel E.; Bello-Pérez, Luis A.; Agama-Acevedo, Edith; Tovar, Juscelino; Aguirre-Cruz, Andres; Alvarez-Ramirez, Jose
Abstract: The formulation of semolina pasta with reduced starch digestibility is of prime importance to deal with the adverse effects of the intake of rapidly digested carbohydrates on human health. This work focused on the effects of the production method (extrusion and lamination) and the addition of commercial Type 2 resistant starch (RS) on the molecular organization and in vitro starch digestibility of semolina pasta. Semolina was substituted with different levels of Type 2 RS for assessing the effect of this dietary fiber. The RS addition reduced the protein solubility and accessible thiols groups, with extruded pasta having higher protein solubility and lower accessible thiols than laminated pasta. Starch ordered structures increased with the RS addition. The increase of the RS in the pasta formulation resulted in a higher α-helix content and decreased β-sheet structures. In vitro starch digestibility was higher for extruded pasta, whilst the levels of RDS and SDS fractions decreased with the addition of RS. It was concluded that the preparation method in combination with RS addition has a determinant impact on the molecular organization and in vitro starch digestibility of semolina-based pasta, providing new insights on the possibilities of improving the health-beneficial features of this widely consumed product. Graphical abstract: Image 1 Highlights: Resistant starch addition reduced the in vitro starch digestibility of semolina pasta. Laminated pasta showed lower in vitro amylolysis rate than extruded pasta. Proteins were differentially altered by the production method. Protein solubility and accessible thiols were lower in sheeting-produced pasta.